Rheology of F620 solder paste and flux - Barbosa, Flávia Vieira (2019)
Purpose The aim of this paper is to characterize the rheological properties of the flux media exposed to different levels of solicitation and to determine its influence on the rheology of the solder paste. The data obtained experimentally are fundamental for the development of numerical models that allow the simulation of the printing process of printed circuit boards (PCB). Design/methodology/approach Rheological tests were performed using the Malvern rheometer Bohlin CVO. These experiments consist of the analysis of the viscosity, yield stress, thixotropy, elastic and viscous properties through oscillatory tests and the capacity to recover using a creep-recovery experiment. The results obtained from this rheological analysis are compared with the rheological properties of the solder paste F620. Findings The results have shown that the flux is viscoelastic in nature and shear thinning. The viscosity does not decrease with increasing solicitations, except in the case where the flow is withdrawn directly from the bottle. Even if the solder paste shows a thixotropic behavior, this is not the case of the flux, meaning that this property is given by the metal particles. Furthermore, the oscillatory tests proved that the flux presents a dominant solid-like behavior, higher than the solder paste, meaning that the cohesive/tacky behavior of the solder paste is given by the flux. Research limitations/implications To complement this work, printing tests are required. Originality/value This work demonstrates the importance of the rheological characterization of the flux in order to understand its influence in the solder paste performance during the stencil printing process.